Enhancing Arabic Language Learning in Islamic Education: Strategies and Challenges - Haq, Amira; Anwar, Najih (Indonesian Journal of Islamic Studies, 2024)
This article delves into the comprehensive approach taken in implementing Arabic language learning at MI Daarul Mutaalimin, encompassing meticulous planning, execution, and evaluation of the learning process. Employing a descriptive qualitative methodology, the study uncovers that the Arabic curriculum at MI Daarul Mutaalimin entails structured lesson planning, involving initial, core, and closing activities. Evaluation is a crucial component. The research identifies key supportive factors such as student enthusiasm, effective teaching methods, appropriate learning media, and strong parental and teacher support. Conversely, hindrances include the use of monotonous media, comprehension difficulties, and diminished motivation. The study advocates remedies like integrating captivating educational tools, dispelling the notion of Arabic as a formidable language, and heightening motivation levels. Highlight: The article provides insights into the holistic approach adopted for Arabic language instruction at MI Daarul Mutaalimin, emphasizing careful planning, execution, and evaluation. Employing a descriptive qualitative methodology, the study underscores the structured nature of the Arabic curriculum, incorporating initial, core, and closing activities within lesson planning. The research highlights crucial factors facilitating the learning process, including student enthusiasm, effective teaching techniques, suitable learning resources, and robust parental and teacher support, while also addressing obstacles like monotonous instructional materials, comprehension challenges, and waning motivation levels. Proposed solutions involve the integration of engaging educational tools, demystifying Arabic's perceived difficulty, and bolstering motivation Keyword: Arabic Language Learning, Islamic Education, MI Daarul Mutaalimin, Comprehensive Approach, Descriptive Qualitative Methodology